Spot kick on racism: Marcus Rashford and criminally damaging penalty shoot-outs - Long, Matt (Hate crime in football, 2023)
In this chapter, we argue that racially motivated vandalism is a social practice which needs to be examined in its own right as much as practices such as antilocution or the verbalization of racist abuse and physical attacks. The empirical context of this chapter rests on the UEFA (Union of European Football Associations) European Football Championship 2020 and the subsequent vandalism of the mural of England football player Marcus Rashford in south Manchester following England’s defeat against Italy in the final. After locating the context of what can be framed as ‘hate vandalism’ as an ideological signifier, the chapter moves on to theorize the intersectional nature of Rashford’s race and class and how, in the current context of Black Lives Matter and child food poverty campaigns, this lends itself to postcolonial narratives. The chapter explores the long history of the mural as an art form whose creation, desecration and sometimes reconstruction have much to offer in terms of forging an understanding of contemporary race and ethnicity in 21st-century Britain.